ADVANCED MANUFACTURING TECHNIQUES AND DIVERSE APPLICATIONS OF COMPOSITE REINFORCEMENT - Ergashev Mahmudjon Mamadjanovich (Western European Studies, 2023)
Composite building materials play a pivotal role in contemporary construction, witnessing continual growth in production. This article addresses the crucial aspects of composite materials, focusing on their production, quality enhancement, and the integration of scientific advancements in capital construction. Emphasizing the need for ongoing improvement, the paper explores refined production processes, heightened material quality, and the application of cutting-edge technologies. Through case studies and real-world applications, it illustrates the transformative impact of innovation on construction practices. The article serves as a concise overview, highlighting the essential role of composite materials in shaping the future of construction. As the demand for robust and sustainable building solutions intensifies, this exploration underscores the imperative to embrace innovation in composite material production, ensuring its continued ascent in the construction industry.
Keywords: Composite building materials; Quality enhancement; Capital construction